The Effect of Brand Familiarity and Perceived Quality on Brand Credibility - Putri, Bilqis Saphira; Yuliana, Lingga (Dinasti Publisher, 2026)
This study aims to analyze the influence of brand familiarity and perceived quality on brand credibility for Vaseline products in Indonesia. This study used a quantitative approach with a survey technique on 170 Vaseline user respondents spread across several urban areas. The research instrument was a questionnaire measured on a Likert scale, and the data were analyzed using the Spearman Rank correlation test. The analysis results show that both independent variables have a positive and significant relationship with brand credibility. These findings confirm that consumer perceptions of product quality, including effectiveness, safety, and consistency, have a greater influence on the formation of brand credibility than the level of brand familiarity alone. The implication of this study is the importance of product quality improvement strategies and communication that focuses on evidence of tangible benefits, so that brand credibility can continue to be strengthened. In the context of the highly competitive skincare market, perceived quality has proven to be the most dominant factor in shaping brand credibility. Therefore, Vaseline needs to maintain consistent product quality and ensure that every product claim can be proven in the eyes of consumers, so that brand credibility is maintained and improved over time.